Expression profile of radiotherapy sensitive genes and tumor-associated immune cell infiltration and prognosis in multiple human cancers. Issue 3 (September 2022) - Li, Guang; Yang, Meng; Ran, Longke; Jin, Fu
Abstract: Radiotherapy sensitive genes (RSGs), as new targets for cancer therapy, combined with tumor microenvironment (TME) and prognosis survival analysis, can provide a new idea for cancer therapy. In this study, RSGs were firstly obtained by searching the literature, then tumor and immune cell data from the Functional Annotation Of Mammalian genomes (FANTOM5) project were analyzed, with definition of two different expression patterns, tumor cell (TC) dominant and immune cell (IC) dominant, and the patterns were verified with RNA-seq data downloaded from the Gene Expression Omnibus (GEO) database. In addition, the correlation between the expression pattern of RSGs and immunotherapy was studied by integrating the seven cancers' radiotherapy data from The Cancer Genome Atlas (TCGA). Result showed that the GEO datasets verification passing rate was greater than 60%. We determined the association between immune infiltration and patients' radiotherapy outcomes, and found that the infiltration levels of Head and Neck Squamous Carcinoma (HNSC) and Uterine Corpus Endometrial Carcinoma (UCEC) in IC-dominated RSGs were higher than those in TC, while the opposite phenomenon was observed in Glioblastoma Multiforme (GBM). The survival analysis of RSGs in seven cancers showed good prognosis in IC (70%) and TC (80%). These findings may help elucidate the influence of tumor-associated immune cell infiltration and prognosis on tumor radiotherapy outcome, which further identified radiosensitive biomarkers of clinical individualized radiotherapy.